2011
DOI: 10.1111/j.1472-4642.2011.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing latitudinal and upstream–downstream gradients: life history traits of invasive mosquitofish

Abstract: Aim  Variation of life history traits along spatial gradients is poorly understood in invasive species and particularly in freshwater fish. We aimed to examine life history variation in a highly invasive fish (Gambusia holbrooki) along latitudinal and upstream–downstream river gradients and to assess the effects of age on this variation. We hypothesized similar responses in populations inhabiting environments more favourable to this species (lower latitudes and lower reaches of rivers). Location  European rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…nutrient enrichment arising from anthropogenic disturbances) tend to be more important influences on fish ecology generally and growth specifically (Lappalainen et al, 2008;Britton et al, 2013). Spatially, the influence of latitude on water temperature is recognised as a major determinant of fish growth rates in the northern hemisphere (Blanck and Lamouroux, 2007;Lappalainen et al, 2008;Carmona-Catot et al, 2011), with a general pattern of reduced growth with increased latitude due to lower temperatures and shorter growth seasons ( (Blanck and Lamouroux 2007;Lappalainen et al, 2008;Carmona-Catot et al, 2011). Nevertheless, anthropogenic activities that modify physical habitats and water quality can also strongly influence growth rates due to the shifts in geomorphic, hydrologic and chemical characteristics of rivers that result in significant changes in the structure and function of fish communities (Welcomme et al, 2006;Beardsley and Britton, 2012;Britton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…nutrient enrichment arising from anthropogenic disturbances) tend to be more important influences on fish ecology generally and growth specifically (Lappalainen et al, 2008;Britton et al, 2013). Spatially, the influence of latitude on water temperature is recognised as a major determinant of fish growth rates in the northern hemisphere (Blanck and Lamouroux, 2007;Lappalainen et al, 2008;Carmona-Catot et al, 2011), with a general pattern of reduced growth with increased latitude due to lower temperatures and shorter growth seasons ( (Blanck and Lamouroux 2007;Lappalainen et al, 2008;Carmona-Catot et al, 2011). Nevertheless, anthropogenic activities that modify physical habitats and water quality can also strongly influence growth rates due to the shifts in geomorphic, hydrologic and chemical characteristics of rivers that result in significant changes in the structure and function of fish communities (Welcomme et al, 2006;Beardsley and Britton, 2012;Britton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced genetic variation in mtDNA among European G. holbrooki populations supports the abovementioned historical records confirming a common source for the majority of these populations and indicates a notorious uniformity among Iberian populations (Vidal et al, 2010). However, substantial genetic diversity at nuclear markers has been observed among Iberian populations from distinct river basins (Vidal et al, 2012;Sanz et al, 2013), as has variation in life-history traits such as size-at-maturity, reproductive effort, and gonadal size (Benejam et al, 2009;Carmona-Catot et al, 2011). Reduced mitochondrial variation and significant nuclear divergence was also observed among introduced populations of the guppy in Australia, and yet substantial adaptive variation was probably conserved in these populations after founder effects related with the introductions (Lindholm et al, 2005).…”
Section: Introductionmentioning
confidence: 48%
“…For each location and 7 cohort, up to 40 individuals were analyzed depending on fish availability (Table 1). Collected fish not displaying gonopodium and smaller than 20 mm were classified as immature, and to ensure that the captured adult fish in a population belonged to a single cohort, only females with a larger standard length than 25 mm and males larger than 20 mm were kept as adults (Carmona-Catot et al, 2011). Thus, the G1 and G3 cohorts were composed of sampled adult fish, and the G2 and G4 resulted from sampled immature fish.…”
Section: Sample Collectionsmentioning
confidence: 99%
“…In a previous paper (Appendix S1 in Carmona-Catot et al [2011]), we provide photographs of scales, with ageing criteria, for some of the same mosquitofish populations. Mosquitofish populations are invariably dominated in number (generally 85-100% of the catch) by young-of-the-year (YOY) that are a few weeks or months old; fish with an annulus (age 1) are generally observed in spring and presumably correspond to fish born in the previous summer; female mosquitofish with two annuli (age 2) are very rare (,1% of the catches) (Tedesco et al 2008b, Carmona-Catot et al 2011. Previous studies into length-frequency distributions of mosquitofish populations (Krumholz 1948, Fernández-Delgado and Rossomanno 1997) described two main cohorts: one consists of individuals that are born in spring, reproduce within a few weeks and mostly die when they are few months old; the other is made up of individuals that are born in summer, are able to overwinter, reproduce early in spring and mostly die before the following summer.…”
Section: Field and Laboratory Methodsmentioning
confidence: 99%
“…For this purpose, we studied the water features and the growth of mosquitofish (Gambusia holbrooki) at 10 river mouths during a 10-month period along a latitudinal gradient of more than 68 along the Mediterranean coast of Spain and France. The eastern mosquitofish G. holbrooki is a suitable model freshwater fish species for these objectives because: (1) it is widespread and abundant in southern Europe, in contrast to many other Iberian freshwater fishes, which are often endemic of a few river basins; (2) their life history traits have been considerably investigated; (3) in many of the same localities sampled in this study, it has been previously shown the above-mentioned weak effects of latitude on life-history traits (Benejam et al 2009, Carmona-Catot et al 2011, although the cause for these patterns are not known, and (4) it is a warmwater fish, which has not invaded northern Europe so far, and temperature affects its growth, reproduction, competitive ability, and survival (Meffe 1992, Pyke 2005, Benejam et al 2009, Carmona-Catot et al 2013. The eastern mosquitofish is a live-bearing poeciliid, native to the eastern USA that has been introduced into freshwater ecosystems worldwide.…”
Section: Introductionmentioning
confidence: 99%